Strategi Pengelolaan Pendidikan Madrasah Aliyah Muhammadiyah di Gorontalo - Muhammad Ramoend Manahung (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2019)
This article analyzes the application of madrasah educational management strategies in Gorontalo Municipality. This study focuses on management in Madrasah Aliyah Muhammadiyah Gorontalo City is the process of implementing curriculum management strategies and the process of applying human resource management strategies. The results showed that, the strategy of managing education in Madrasah Aliyah Muhammadiyah Gorontalo. First, the application of curriculum management strategy consists of planning, namely the implementation of curriculum planning activities always involve all elements, the madrasah head participates in overcoming difficulties, supervision and assessment shows the results of the final stage evaluation (odd semester test) is quite good. Second, the implementation of Human Resources management strategies, namely teachers and employees appear professional in terms of: time attendance discipline, return, and neatness, carrying out tasks and responsibilities properly and professionalism of teachers in managing classes and changes in student behavior.